Positive parenting: link with the child’s mental health - Antão, Celeste (2020)
Compliance with the fundamental principles of equality and non-discrimination, the right to privacy, autonomy, the right to information that are enshrined in international agreements and the Universal Declaration of the Rights of the Child is the beginning of the promotion of good mental health for the child. Objective: to emphasize the relationship of parental behavior in the child’s mental health. Methodology: exploratory study within the scope of the theme in order to emerge contributions in improving children’s mental health. Volume 4 Issue 5 - 2020 Celeste Antão Instituto Politécnico de Bragança, Campus de Santa Apolónia, Bragança, Portugal Correspondence: Celeste Antão, Instituto Politécnico de Bragança, Campus de Santa Apolónia, Bragança, Portugal, UICISA: E-Higher School of Health, Email Received: August 23, 2020 | Published: September 14, 2020 Results: A positive parenting with healthy interaction, security and good behavior management are undoubtedly promoters of good mental health. Conclusion: The training of parents as caregivers, an example of a child’s learning through imitation processes.